Distribution of fishing grounds of longline sharks based in Ujung Serangga Fishing Base, Southwest Aceh, Aceh - Rahmah Alvi; Aprilla Ratna Mutia; Dwi Okta Rosi; Fathanah Yusuf (BIO Web of Conferences)
The number and size of shark catches at Ujung Serangga Fish Landing Base have declined, while the operational area of shark longlines has expanded since 2015. This research aims to determine the distribution of longline fishing grounds and the composition of the shark catches for longlines based in Ujung Serangga Fish Landing Base. This research was done in 2024, March to April at Ujong Serangga Fish Landing Base, Padang Baru Village, Susoh District, Southwest Aceh Regency. The research method is descriptive. The results showed that shark catches were most common in the Mentawai waters of Siberut Island and Pagai Island. During the research, sharks landed at Ujung Serangga Fish Landing Base totaling 296 individuals with a total of 8 species. The dominant shark during the study was the lanjaman shark (Carcharhinus falciformis) with a total of 147 individuals (49.66%) and spotted tail shark species (Carcharhinus sorrah) as many as 82 individuals (27.70%). The least caught shark species were the great hammerhead shark (Sphyrna mokkaran) with 1 individual (0.34%), tiger shark (Galeocerdo cuvier) with 1 individual (0.34%), and silvertip shark (Carcharhinus albimarginatus) with 1 individual (0.34%). The longline sharks based at Ujung Serangga Fish Landing Base have 9 fishing locations consisting of Ujung Batu Island, Gunung Sitoli Island, Asu Island, Siberut Island, Hinako Island, Bangkaru Island, Simuk Island, Pini Island and Pagai Island.